Zarządzanie gospodarką wodną w Polsce - Miłaszewski, Rafał (Management of water economy in Poland, 2007)
In Poland, in accordance with the assumptions of the European Union Water Framework Directive, actions have been undertaken aiming at implementing integrated management of water resources in the catchment systems. This form of management, concurrent with the constitutional principle of sustainable development, is implemented by means of three strategie water management objectives discussed in the paper. In addition, other issues comprising water resources management, i.e. the legał basis of water economy, the framework of the management system and water management instruments are reviewed in the paper. Particular attention is focused on water management planning in the catchment areas as well as on activities which, taking under consideration the Polluter Pays Principle, should lead to optimal water services cost recovery by the year 2010.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1190, s. 283-293